PENGARUH PENGGUNAAN BEBERAPA JENIS FILLER TERHADAP PALATABILITAS CHICKEN NUGGET AYAM PETELUR AFKIR - Sakul, Sjaloom; Komansilan, Sylvia (ZOOTEC, 2018)
THE INFLUENCE OF THE USE OF VARIOUS FILLERS TOWARDS THE PALATABILITY OF CHICKEN NUGGET. The objectives in this research is to observe and study the fillers that vary in producing the formulation of chicken nugget which were received by the consumers observed from the physical. This research was conducted at the Laboratory of Animal Science Sam Ratulangi University Manado, The Laboratory of Nutrient Fakulty of Animal Husbandry Sam Ratulangi University Manado. The material used in this research was meat and fat of non-productive layer (culled) as much as 6400 gram, devided into 16 samples, each sample weighed 100 gram fat and 300 gram meat. The research was carried out through an experient, a completely randomized design with four replications. The fillers Used in this treatment are; T1 (Sago), T2 (Tapioka) T3 (Maizena), T4 (Glutten Rice). The Quality of chicken nugget according to the parameter ini this research was as follows; the palatability (Taste, texture, tenderness and general acceptance). From the result of this research it was concluded that the filler which used tapioca (T2) and Sago (T1), had produced chicken nugget which was much better, compared to the use of maizena (T3), glutten rice flour (T4), and generally accepted by the consumers, supported by their characteristics.Keyword: Palatability, Filler, Chicken Nugget, Organoleptic